2013
DOI: 10.3324/haematol.2013.096545
|View full text |Cite
|
Sign up to set email alerts
|

Gemtuzumab ozogamicin in combination with vorinostat and azacitidine in older patients with relapsed or refractory acute myeloid leukemia: a phase I/II study

Abstract: The primary objective of this study was to determine the vorinostat dose with the most favorable efficacy and toxicity when combined with azacitidine and GO. Methods Study population

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 27 publications
0
24
0
1
Order By: Relevance
“…Azacitidine-based combinations have recently been investigated in early phase clinical trials in relapsing/refractory AML [76][77][78] and in retrospective cohorts of limited size [60,69,79,80]. Subgroups of relapsed/refractory patients likely to benefit from such azacitidine-based regimens have not been identified to date.…”
Section: Combinationmentioning
confidence: 98%
“…Azacitidine-based combinations have recently been investigated in early phase clinical trials in relapsing/refractory AML [76][77][78] and in retrospective cohorts of limited size [60,69,79,80]. Subgroups of relapsed/refractory patients likely to benefit from such azacitidine-based regimens have not been identified to date.…”
Section: Combinationmentioning
confidence: 98%
“…94 Although GO is not easily available outside clinical trials, we try to get this drug based on published evidence in elderly relapsed patients with CD33 expression of the blasts as a bridge to transplantation. 95 GO has also been used in combination with demethylating agents such as vorinostat 96 or AZA. 97 These preliminary studies are especially promising for patients not tolerating intense chemotherapy, and modifications of the antibody and its linker might lead to further improvement.…”
Section: Targeting Cd33mentioning
confidence: 99%
“…Gemtuzumab ozogamicin was granted accelerated approval by the FDA in 2000 for the treatment of patients over 60 years of age with relapsed CD33-positive AML (3), but was voluntarily withdrawn in 2010 when a postapproval commitment study failed to confirm clinical benefit and hepatic sinusoidal obstruction syndrome (SOS) became recognized as an adverse event (4)(5)(6). However, several recent clinical trials have clarified the optimal conditions for gemtuzumab ozogamicin use and demonstrated benefits to specific patient populations (7,8). Currently, gemtuzumab ozogamicin is still approved and available in Japan.…”
Section: Introductionmentioning
confidence: 99%